Judges' Capacity to Evaluate Psychological and Psychiatric Expert Testimony. Issue 3 (2nd July 2016) - Tadei, Alessandro; Finnilä, Katarina; Reite, Agnetha; Antfolk, Jan; Santtila, Pekka
Abstract: We examined the criteria judges in Finland perceive as important when evaluating the quality of expert testimony, and how judges question psychological and psychiatric expert witnesses to determine the reliability of their testimony. The 87 participating judges rated the importance of the following criteria for the credibility of expert testimony: expert's work experience, expert's research activity, falsifiability, error rate, peer-reviewed research, scientific acceptance, and practical acceptance. The judges were thereafter given five vignettes describing expert testimony and asked about the questions they would present to the expert witness about each case. The results show that the judges considered the expert's work experience to be the most important criterion when judging the reliability of expert evidence. Also, the questions they would ask to assess the reliability of the testimony are consistent with these results. However, as the judges mostly asked questions that could not directly be categorized into any of the seven categories, additional categories were created. These additional categories reveal that many judges ask a more general question concerning the testimony. The present study indicates that the judges are not sufficiently equipped to correctly evaluate expert testimony.